Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

Solve the following problem:

5x - 3 = 4x + 3

A. x = 5

B. x = 6

C. x = 7


Sagot :

Answer:

x=6

Step-by-step explanation:

Step 1: Subtract 4x from both sides.

5x−3−4x=4x+3−4x

x−3=3

Step 2: Add 3 to both sides.

x−3+3=3+3

x=6

Answer:

B.

Step-by-step explanation:

5x-3+3=4x+3+3

5x=4x+6

5x-4x=4x+6-4x

x=6